Evolution of global polio eradication strategies: targets, vaccines, and supplemental immunization activities (SIAs) - Kimberly M. Thompson; Kamran Badizadegan (Taylor & Francis Group, 2024)
Background Despite multiple revisions of targets and timelines in polio eradication plans since 1988, including changes in supplemental immunization activities (SIAs) that increase immunity above routine immunization (RI) coverage, poliovirus transmission continues as of 2024.Methods We reviewed polio eradication plans and Global Polio Eradication Initiative (GPEI) annual reports and budgets to characterize key phases of polio eradication, the evolution of poliovirus vaccines, and the role of SIAs. We used polio epidemiology to provide context for successes and failures and updated prior modeling to show the contribution of SIAs in achieving and maintaining low polio incidence compared to expected incidence for the counterfactual of RI only.Results We identified multiple phases of polio eradication that included shifts in targets and timelines and the introduction of different poliovirus vaccines, which influenced polio epidemiology. Notable shifts occurred in GPEI investments in SIAs since 2001, particularly since 2016. Modeling results suggest that SIAs play(ed) a key role in increasing (and maintaining) high population immunity to levels required to eradicate poliovirus transmission globally.Conclusions Shifts in polio eradication strategy and poliovirus vaccine usage in SIAs provide important context for understanding polio epidemiology, delayed achievement of polio eradication milestones, and complexity of the polio endgame.